STRATEGI PENYESUAIN DIRI ANGGOTA KELUARGA LEOBISA SETELAH BERHENTI MELAKUKAN RITUAL MEMBERI MAKAN BUAYA DI KOLBANO - Claudia Pramila Nailius; Emmanuel Satyo Yuwono (Jurnal Inovasi Penelitian, 2023)
The ritual of feeding crocodiles to the Timorese people, especially in the village of Kolbano, has been going on for a long time and has become an important element of local people's lives. However, as time went on, ritual activity began to fade, starting from the colonial period and the spread of Christianity became the starting point for the tradition of feeding crocodiles. The people who performed the ritual had to be dismissed and had to follow the rules of Christian teaching. It was from this incident that the Kolbano village community had to adapt themselves, especially members of the Leobisa family who were the perpetrators of the crocodile feeding ritual. The purpose of this study was to find out the adaptation strategies carried out by actors when they stopped performing rituals. This study uses qualitative research methods with a descriptive-phenomenological approach to collecting data using interview and observation techniques. The results of the study show that there is an interpersonal relationship with the family, work activities as stress coping, and a positive self-image as an adjustment strategy.